(3JMaI Cgd GdUOjbjI HCSGfjO GdWGFaI GdLRhdjI hGdQRhbjIs - (3GdaGSj , eMeO Hf CMeO Hf Ydj Hf jhSa, CHh YHO Gddg,J (B1109 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR ChdjGDg GdeJbjf gPG hEfg deG cGf ZGdH Cgd Gddg HbWQfG gPG ai gGJjf GdeGFJjf , GdYGTQI hGdMGOjI YTQI JQLY Edi TjNjf s
(3BNQgG (B:s
(3gPg GdSdSdI gi GdJj YfO CcKQ eJabQI GdYUQ ef Cgd GdeZQH hgj dGJUM CUdG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B151s
(3aj Chd GdfSNI CKGQ JeRjb hWeSs
(3hYdi GdfSNI GSe BNQ gh JMaI Cgd GdJUOjb HCSGfjO GdWGFaI GdLRhdjI hGdQRhGbjI ef Cgd GdWQjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B301s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B462 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B703 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B95 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs